Application of predictive nursing based on Plan-Do-Check-Action cycle in prevention of falls in long-stay senile psychiatric patients (PDCA循环式预见性护理在预防长期住院老年精神科患者跌倒中的应用) - ZHANG Xiaoning (张晓宁); ZHANG Peifeng (张培峰); TANG Xiaofang (唐晓芳); YANG Ping (杨平); WU Xiaorong (邬晓蓉); LI Dongmei (李东梅) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of predictive nursing based on Plan-Do-Check-Action(PDCA) cycle in prevention of falls in long-stay senile psychiatric patients. Methods Totally 140 senile psychiatric patients with hospital stay more than one year were included as the control group. After implementation of predictive nursing based on PDCA cycle, another 140 senile psychiatric patients with hospital stay more than one year were recruited as the observation group. To compare the incidence of falls and related nursing quality scales between two groups. Results Two cases in the observation group were lost to follow-up. There were 8 (5. 80%)cases of falls in the observation group and 20(14. 29%) cases of falls in the control group, with a significant difference (P＜0. 05). The scores of nursing quality in aspects of management, implementation, equipment and environment, education and feedback were higher than those in the control group(P＜0. 05). Conclusion The predictive nursing based on PDCA cycle is effective to reduce the risk of falls in long-stay senile psychiatric patients. (目的 探讨PDCA循环式预见性护理在预防长期住院老年精神科患者跌倒中的应用效果。方法 选取2019年1月1日前在苏州市广济医院精神科住院时间≥1年的患者140例作为对照组, 另选取2019年1月1日起施行PDCA式预见性护理后住院时间≥1年的患者140例患者为观察组, 观察2组跌倒发生情况, 比较2组防范患者跌倒护理质量。结果 观察组2例患者退出研究。观察组发生跌倒8(5. 80%)例, 对照组发生跌倒20(14. 29%)例, 2组比较差异有统计学意义(P＜0. 05)。观察组组织管理、措施落实、设备环境及宣教反馈评分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 PDCA循环式预见性护理能有效降低长期住院老年精神科患者跌倒风险, 提高护理质量。)